Augmentative releases of Dactylopius austrinus De Lotto (Dactylopiidae; Hemiptera) for biological control of Opuntia aurantiaca Lindley (Cactaceae), in South Africa - Mulateli, Thifhelimbilu (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2019)
Opuntia aurantiaca Lindely (Cactaceae) is an invasive alien cactus which has detrimental effects on agroecosystems and indigenous biodiversity in South Africa. Dense infestations over large areas reduce grazing capacity and indigenous biodiversity. Despite the release of a biological control agent, the cochineal insect Dactylopius austrinus De Lotto (Dactylopiidae), the weed is still considered a major problem in many parts of the country. Biological control has relied heavily on classical biological control, with little augmentative biological control implemented. This study investigated the outcome of mass-rearing and augmentative releases of D. austrinus for the control of O. aurantiaca. Augmentative releases are thought to improve the level of control by increasing agent densities in the field and thus increasing the level of damage inflicted to the plants. All data were collected with the intention to optimize release strategies so that the maximum benefit from the biological control agent could be achieved. An impact study was conducted using potted plants in a greenhouse to quantify the efficacy of multiple releases of the agent on the target weed. All three of the release treatments showed consistently higher proportion of cochineal than the controls, as well as the insect exclusion treatments, and these differences were statistically significant. The number of cladodes per plant increased significantly for the insect exclusion and control treatment over the period of the study, whilst all three release treatments decreased steadily over the same period. This study indicated that the agent is damaging to O. aurantiaca and that a single release event was beneficial but that multiple releases did not result in greater levels of control. A post-release evaluation was carried out to quantify the impact of releases of D. austrinus on O. aurantiaca in the field. Plots where the agent was excluded were compared with those where the agent was left at natural field densities and three treatments where agent populations were augmented to varying degrees through releases. The percentage of cochineal infested cladodes for all treatments decreased over time from the initiation of the experiment in October 2017 until the end of the experiment in October 2018. Opuntia aurantiaca densities also decreased over time for all treatments. The insect exclusion treatment had the greatest number of plants for the duration of the study, but this was not significantly different from other treatments. Dactylopius austrinus was damaging to O. aurantiaca, but climatic conditions in the field limited the efficacy of releases. Although O. aurantiaca density decreased during the experiment, it was evident that the reduced number of plants was not due to augmentation of the cochineal populations from the releases that were conducted. The experiment was conducted over a very dry period, when cochineal was particularly effective, so although augmentative releases did not improve the level of control, the natural population of cochineal was high and very damaging to O. aurantiaca over the course of the experiment. Releasing during wet periods, when the agent is less effective, could augment agent populations at a time when natural populations would be low, and hence improve levels of control further. Although this study was limited to a short period of two years, the results of this study suggest that the number of releases is less important than the timing of releases. Releasing immediately after periods of high rainfall is likely to be beneficial, while releasing during dry periods, or during winter when temperatures are low, is less effective. Dactylopius austrinus populations should be constantly monitored so that releases can be conducted when cochineal populations are low and the climatic conditions are correct. If the timing of release events is appropriate, then the over level of control of O. aurantiaca using D. austrinus could be improved.
Keywords: Opuntia aurantiaca -- Biolotical control -- South Africa; Invasive plants -- Biolotical control -- South Africa; Dactylopius austrinus De Lotto -- South Africa; Dactylopius -- South Africa